The Archives Testify - Operation Teutonic Sword - Thorndike, Andrew; Thorndike, Andrew; Thorndike, Annelie; Thorndike, Annelie; Fuchs, Walter; Kunstmann, Vera; Perin, Gustl (IHF, 2014)
An incendiary piece of Cold War polemic, this 1957 film accuses General Hans Speidel - at the time Commander-in-Chief of Allied NATO forces - as a key accomplice in Hitler's 1934 assassination of King Alexander I of Yugoslavia and Louis Barthou of France. Speidel, who served as a leading commander in the Wehrmacht in World War 2, is also charged with having betrayed Field Marshal Erwin Rommel in 1944's failed Officers' Plot to kill Hitler. The movie sparked vociferous protest and legal action by Speidel, whose lawsuits led to its British distributors being tried before the House of Lords in 1961. [ihffilm.com]
Keywords: DVD-Video